Entrepreneurial Skills dan Entrepreneurial Attitude Mahasiswa Akuntansi - Mashuda, Ahmad; Laily, Nujmatul (Universitas Negeri Surabaya, 2021)
This research is motivated by the high unemployment rate in Indonesia at the diploma and undergraduate level due to limited employment opportunities. This study aims to determine whether entrepreneurial skills (risk taking skills, innovation skills, leadership skills, communication skills, and problem solving skills) affect students' entrepreneurial attitudes. Quantitative methods are used to answer the research problems. The respondents were 97 Accounting students who were taken using accidental sampling technique while the analysis used multiple linear regression analysis. The results showed that risk taking skills and innovation skills had an effect on entrepreneurial attitudes. Meanwhile, leadership skills, communication skills, and problem solving skills have no effect on entrepreneurial attitudes.